Campus Canopy, 1945-04-15 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1945)
Home Ec. Club Hears Authorities On Ec. As Vocation -- GSWC Hair Fads -- GSWC Holds Memorial Services For Franklin D. Roosevelt Friday Morning -- Broadmindedness Comes From Hobbies, Points Out Butler -- Bentley To Be Next President of Home Ec. Club
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals